A systematic review on public perceptions of RNAi-based biopesticides: Developing Social Licence to Operate - Raquel Tardin-Coelho; Stephen Fletcher; Narelle Manzie; Sandya Nishanthi Gunasekara; Pedro Fidelman; Neena Mitter; Peta Ashworth (npj Sustainable Agriculture)
Abstract Agriculture is fundamental to ensuring humanity’s food and fibre security. Synthetic pesticides pose challenges due to resistance, emissions, toxicity, and harm to beneficial organisms. A novel approach involves RNA-based biopesticides, eliciting an RNA interference (RNAi) response via topical application of double-stranded RNA (dsRNA), avoiding genetic modification. However, potential issues surrounding RNAi, including policy controversies and regulatory gaps, may affect public perception and acceptance of topical RNAi, impacting the acquisition of a social licence to operate (SLO). This qualitative systematic literature review examines public perceptions of RNAi-based biopesticides, the associated policy considerations and their implications for developing an SLO. The results show that factors influencing public perceptions and SLO emphasise human and environmental safety and costs, including also off-target impacts, degradability, protection window, resistance, toxicity, and ethical and cultural considerations. Finally, we discuss strategies from social science literature for RNAi-biopesticides to achieve an SLO towards sustainability, enhancing food safety and productivity.